Fortification of the suburb of the Great Moravian stronghold at Mikulčice-Valy - Hladik, Marek; Hadacz, Roman; Dohnalová, Alena; Šušolová, Jana; Látková, Michaela; Kynický, Jindřich (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2014)
The aim of the paper is to present the fortification of the suburb of the early medieval central agglomeration of Mikulčice-Valy. Methodically seen, the work is based on three pillars: post-excavation analyses of old documentary materials from fieldwork (GIS, spatial analyses, stratigraphy), modern excavations focused on obtaining as many as possible exact data, and subsequent environmental analyses. Postexcavation analyses of fieldwork documentation from excavations of the fortification in 1960-1977 together with knowledge from the 2012 field research aim to answer three basic questions: original dating of the defensive wall (its origin and demise), description of relics of its functional elements and building reconstruction, and identification of events which induced the build-up and subsequent demise of this structure. The results of analyses performed provide a base for discussion about the hypotheses of chronology and construction of the defensive wall, which were published by Z. Klanica, J. Poulík and B. Kavánová in the second half of the 20th century. In the end the authors present an interpretational model of dating, construction and demise of the fortification in the suburb of the Mikulčice agglomeration.